2010
DOI: 10.1094/pdis-94-8-1015
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Tomato with Interspecific Rootstock to Manage Diseases Caused by Sclerotium rolfsii and Southern Root-Knot Nematode

Abstract: Southern blight (Sclerotium rolfsii) and root-knot nematodes (Meloidogyne spp.) cause severe damage to fresh-market tomato (Solanum lycopersicum) throughout the southeastern United States. Grafting is an emerging technology in U.S. tomato production, and growers require information regarding the resistance characteristics conferred by rootstocks. In this study, southern blight (SB) and root-knot nematodes (RKN) were effectively managed using interspecific hybrid rootstocks. During 2007 and 2008, field trials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 20 publications
(44 reference statements)
3
66
2
Order By: Relevance
“…Rivard et al (2010) observed that in an area under high pressure from M. incognita, nongrafted tomatoes were severely damaged. These authors evaluated three rootstocks for tomato and observed that 'Maxifort' and 'Beaufort' had low incidence of galls Resistance confirmation whereas 'Big Power' only had traces of galls.…”
Section: Resultsmentioning
confidence: 99%
“…Rivard et al (2010) observed that in an area under high pressure from M. incognita, nongrafted tomatoes were severely damaged. These authors evaluated three rootstocks for tomato and observed that 'Maxifort' and 'Beaufort' had low incidence of galls Resistance confirmation whereas 'Big Power' only had traces of galls.…”
Section: Resultsmentioning
confidence: 99%
“…Kacjan Maršić and Jakše (2010) also indicated the 'RS 841 Improved' as a rootstock that could provide better marketable yield and fruit number when compared to ungrafted plants. The study of Rivard et al (2010) was also conducted in a field that was naturally infested with a population of RKN, and showed that tomato fruit yield was higher for plants grafted onto resistant rootstocks. Similarly, Verdejo-Lucas and Sorribas (2008) conducted a study with grafted tomato plants in the soil artificially infested with Meloidogyne javanica and reported a higher cumulative yield in the resistant cultivar than in the susceptible control.…”
Section: Discussionmentioning
confidence: 99%
“…However, grafting of tolerant rootstocks, as an alternative to pesticide use, may be a more sustainable approach particularly for organic production. The usage of the RKN-resistant rootstocks has been successful in tomato, but is dependent on the RKN species present, the local RKN population within the species, and on the genetic background of tomato with regard to the Mi gene (Lopez-Perez et al, 2006;Cortada et al, 2008;Verdejo-Lucas et al, 2009;Rivard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Source: Bolandnazar et al, 2014;Rivard et al, 2012;Keatinge et al, 2014;Onduso, 2014;Vitale et al, 2014;Hibar et al, 2006;Kaskavalci et al, 2009;Mochizuki and Yamakawa, 1979;Jang et al, 2012;Al-Chaabi et al, 2009;Rivard et al, 2010. Lee et al, (2010); Pandey and Rai (2003); Penella et al, 2014;AVRDC 2003AVRDC & 2009 The majority of users of grafted seedlings is currently greenhouse hydroponic tomato growers, whereas it is still a relatively unknown technique for open-field vegetable growers.…”
Section: Challenges In Graftingmentioning
confidence: 99%